Sustainability and Climate Services: Critique, Integration, and Reimagination - Herrick, Charles; Vogel, Jason; Anderson, Glen Douglass (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
For a long time, the entry point for most communities and decision makers concerned about climate change was to ask, "what does the science tell us is going to happen?" Consequently, even though some effort was made to bring social and policy sciences to bear with the climate services enterprise, the demand for technological advances such as downscaled climate model projections and climate impact science drove much of the climate services agenda during its first decade and a half. By the 2000s, 'users' of climate information were becoming more sophisticated, and demand-driven innovations began to be recognized in peer-reviewed discussions of climate services; nevertheless, most authors continue to privilege a top-down, science-first flow of knowledge production and innovation. Entitled "Sustainability and Climate Services: Critique, Integration, and Reimagination," the purpose of this Special Issue of Sustainability is to empower unconventional thinking in the hopes of accelerating the relevance of climate services at a time when communities at all levels are pursuing programs of adaptation, resilience, and sustainability. It is our hope that this Special Issue will provide outside-the-box, but constructive, critique to help support the basis for a 'next generation' of weather- and climate-related information products and services.